Challenges to Antimicrobial Stewardship in the Countries of the Arab League: Concerns of Worsening Resistance during the COVID-19 Pandemic and Proposed Solutions - Nesrine A. Rizk; Rima Moghnieh; Nisrine Haddad; Marie-Claire Rebeiz; Rony M. Zeenny; Joya-Rita Hindy; Gabriella Orlando; Souha S. Kanj (MDPI AG, 2021)
The COVID-19 pandemic is expected to worsen the global problem of antimicrobial resistance (AMR). There is a heightened interest in understanding this effect and to develop antimicrobial stewardship (AMS) interventions accordingly to curb this threat. Our paper aims to evaluate the potential magnitude of COVID-19 on AMR and AMS with a focus on the countries of the Arab league, given the social, political, and economic environments. We also evaluate obstacles in applying the rational use of antibiotics, monitoring resistance trends in the midst of the pandemic, and evaluating the impact of the economic crisis in some countries. We aim to raise awareness about the potential effects of antibiotic overuse during the pandemic and to propose practical approaches to tackle this issue.